Pengaruh Tendon And Nerve Gliding Exercise Terhadap Penurunan Nyeri Pada Penderita CTS ( Carpal Tunnel Syndrome ) - Dini Nur Alpiah; Putri Utami Ningsih (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Carpal Tunnel Syndrome (CTS) is a peripheral neuropathy caused by compression of the median nerve in the carpal tunnel, causing pain, paresthesia, and impaired hand function. Various physiotherapy interventions have been used as conservative therapy for CTS, but their effectiveness varies. Objective: To determine the effectiveness of physiotherapy interventions on reducing pain and improving hand function in CTS patients based on seven research journals. Methods: This study is a literature review of seven national and international journals published between 2020 and 2025. Articles were selected based on topic suitability, experimental design, and the availability of pre- and post-intervention data. Results: All journals showed a significant reduction in pain and improvement in hand function in the experimental group compared to the control group. Conclusion: Physiotherapy interventions such as nerve gliding exercises, tendon gliding exercises, neural mobilization, and manual therapy are effective in treating CTS.